Genome of Superficieibacter maynardsmithii, a novel, antibiotic susceptible representative of Enterobacteriaceae - Biffignandi Gherard Batisti; Gibbon Marjorie J.; Corbella Marta; Thorpe Harry A.; Merla Cristina; Castelli Michele; Kallonen Teemu; Pegrum Katie; Brisse Sylvain; Corander Jukka; Marone Piero; Feil Edward J.; et al. (Genetics Society of America, 2022)
During a citywide microbiological screening project in Pavia (Italy) a bacterial strain isolated from the surface of an Automated Teller Machine was classified as a Klebsiella sp. by MALDI-TOF spectrometry, and shown to be susceptible to the most antimicrobial classes by phenotypic testing. After Illumina genome sequencing and subsequent assembly, a high-quality draft genome was obtained (size = 5,051,593 bp, N50 = 615,571 bp, largest contig = 1,328,029 bp, N_contig = 17, GC content = 51.58%, coverage = 141.42), absence of antimicrobial resistance genes was confirmed, but the strain resulted to be highly divergent from all Klebsiella, and more related to other Enterobacteriaceae. The higher values of 16S rRNA identity were with members of the genera Citrobacter, Salmonella, and “Superficieibacter.” An ortholog-based phylogenomic analysis indicated a sister group relationship with “Superficieibacter electus,” in a distinct clade from other members of the Enterobacteriaceae family. In order to evaluate whether the novel genome represents a new species of “Superficiebacter,” average nucleotide identity (ANI) and Hadamard analysis were performed on a dataset of 78 Enterobacteriaceae. The novel genome showed an ANI of 87.51% with S. electus, which compared on identity values between other members of the family, clearly indicates that the genome represents a new species within the genus “Superficieibacter.” We propose for the new species the name “Superficieibacter maynardsmithii.”